2018
DOI: 10.3390/su10020542
|View full text |Cite
|
Sign up to set email alerts
|

A Regional Analysis of the Life Cycle Environmental and Economic Tradeoffs of Different Economic Growth Paths

Abstract: Different economic development strategies may result in varied socioeconomic and environmental synergies or tradeoffs, suggesting an opportunity for environmentally conscious planning. To understand such synergies or tradeoffs, a dynamic environmental life cycle assessment was conducted for eleven groups of New Hampshire industries. Historical state level Gross Domestic Product (GDP)-by-industry data was combined with economic input-output analysis to calculate the direct and life cycle energy use, freshwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The literature on the assessment of GHG emissions in specific sectors such as agriculture, industry, energy, transport, construction, or tourism is quite extensive [15,46,47], and as can be observed, the methods of analysis are diverse, with authors mainly attempting to analyze the potential for GHG emission reductions [17,24,25,46,48,49], the past changes and future trends in GHG emissions, environmental impacts, and mitigation actions [16,47]. Sector-specific studies have shown that the best strategy to grow GDP with less environmental impact is to develop some advanced technologies [47].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on the assessment of GHG emissions in specific sectors such as agriculture, industry, energy, transport, construction, or tourism is quite extensive [15,46,47], and as can be observed, the methods of analysis are diverse, with authors mainly attempting to analyze the potential for GHG emission reductions [17,24,25,46,48,49], the past changes and future trends in GHG emissions, environmental impacts, and mitigation actions [16,47]. Sector-specific studies have shown that the best strategy to grow GDP with less environmental impact is to develop some advanced technologies [47].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the Government should not only regulate the logistics and sustainable aspects during the procurement of raw materials, production process, and distribution of finished products; it must also regulate the reprocessing of materials after the life of the product has finished [27]. For example, in Shu [20] reported a study in which there are useful components for remanufacturing, which is done with Government subsidies, and Mo [28] presented a study of the analysis of the life of products that have intellectual property rights. Therefore, it is observed that the sustainability of companies and their supply chains is widely associated with regulations given by Government, so it is currently considered that it must be fully committed to the establishment of sustainable standards and monitor their compliance, and for this reason, the Government is declared to be one of the pillars of sustainability, and should be the main promoter of that culture [29].…”
Section: Government Supply Chain and Sustainabilitymentioning
confidence: 99%